Diagnosis and management of adult coeliac disease: guidelines from the British Society of Gastroenterology. Issue 8 (10th June 2014) - Ludvigsson, Jonas F; Bai, Julio C; Biagi, Federico; Card, Timothy R; Ciacci, Carolina; Ciclitira, Paul J; Green, Peter H R; Hadjivassiliou, Marios; Holdoway, Anne; van Heel, David A; Kaukinen, Katri; Leffler, Daniel A; et al.
Abstract : A multidisciplinary panel of 18 physicians and 3 non-physicians from eight countries (Sweden, UK, Argentina, Australia, Italy, Finland, Norway and the USA) reviewed the literature on diagnosis and management of adult coeliac disease (CD). This paper presents the recommendations of the British Society of Gastroenterology. Areas of controversies were explored through phone meetings and web surveys. Nine working groups examined the following areas of CD diagnosis and management: classification of CD; genetics and immunology; diagnostics; serology and endoscopy; follow-up; gluten-free diet; refractory CD and malignancies; quality of life; novel treatments; patient support; and screening for CD.